2005
DOI: 10.1038/sj.onc.1208583
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen regulated induction of FRA-1 proto-oncogene is controlled by the transcription factors binding to both serum and TPA response elements

Abstract: FRA-1, a member of the FOS family of transcription factors, is overexpressed in a variety of human tumors, and contributes to tumor progression. In addition to mitogens, various toxicants and carcinogens persistently induce FRA-1 expression in vitro and in vivo. Although the mitogen induced expression of c-FOS is relatively well understood, it is poorly defined in the case of FRA-1. Our recent analysis of the FRA-1 promoter has shown a critical role for a TRE located at À318 in mediating the TPA-induced expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 37 publications
4
51
0
Order By: Relevance
“…We have recently shown that FRA-1 up-regulates the expression of genes involved in airway squamous metaplasia (8). The expression of FRA-1 is persistently induced in bronchial epithelial cells by lung carcinogens such as tobacco smoke (9), tumor-promoting phorbol esters, and mitogens (10,11). Consistent with these observations, overexpression of FRA-1 has been noted in squamous cell carcinomas of the head and neck (12), esophagus, and stomach (13).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…We have recently shown that FRA-1 up-regulates the expression of genes involved in airway squamous metaplasia (8). The expression of FRA-1 is persistently induced in bronchial epithelial cells by lung carcinogens such as tobacco smoke (9), tumor-promoting phorbol esters, and mitogens (10,11). Consistent with these observations, overexpression of FRA-1 has been noted in squamous cell carcinomas of the head and neck (12), esophagus, and stomach (13).…”
Section: Introductionsupporting
confidence: 61%
“…The results of assays measuring three-dimensional Matrigel migration and invasion and soft agar growth revealed that FRA-1 overexpression greatly enhances both the growth and invasive potential of lung epithelial cells. We have previously shown that various agents that promote tumor cell growth and invasion persistently activate FRA-1 expression in pulmonary (type II and bronchial) epithelial cells (9)(10)(11)20). Thus, the present findings are important in that the activation of this transcription factor by mitogens and carcinogens plays key roles in promoting cell growth, malignant transformation, and invasive potential of pulmonary epithelial cells.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, recent data point to a positive effect of Fra-1, and partly Fra-2, on tumor invasion and progression in many tumor types (110,111). Moreover, a model was proposed in which both Fra-1 and c-Fos act as adaptors for other transcription factors, or as transcriptional repressors rather than transcriptional activators (112).…”
Section: Ap-1 As a Potential Treatment Target In Respiratory Epithelimentioning
confidence: 99%
“…114). Yet, most data concerning the function of Fra-1 in respiratory epithelium carcinogenesis are based on experimental results, and the role of these transcription factors in clinical tumors is still obscure (110). In most of the tumor tissues analyzed thus far, Fra-1 expression has been found far below the protein amounts detected in undifferentiated cell lines, and the electrophoretic mobility of the Fra-1 protein indicates that it is not highly phosphorylated, which might lead to its stabilization and in vitro activation (40).…”
Section: Ap-1 As a Potential Treatment Target In Respiratory Epithelimentioning
confidence: 99%